2018
DOI: 10.1089/hum.2017.072
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy with an Adeno-Associated Viral Vector Expressing Human Interleukin-2 Alters Immune System Homeostasis in Humanized Mice

Abstract: Recombinant adeno-associated viruses (rAAVs) serve as vectors for in vivo gene delivery in both mice and humans, and have broad applicability for the treatment of genetic diseases. Clinical trials with AAV vectors have demonstrated promise and safety in several human diseases. However, the in vivo validation of novel AAV constructs expressing products that act specifically on human cells and tissues is limited by a paucity of effective translatable models. Humanized mice that are engrafted with human cells, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…3), we next determined whether administration of human recombinant IL-2 could modulate the T cell populations. We have previously shown that administration of a dsAAV8 vector encoding human IL-2 (dsAAV8-huIL-2) increased human regulatory T (T reg ) cells in NSG mice humanized by engraftment of human fetal liver and thymus [i.e., the BLT model (49)]. In the current study, injection of dsAAV8-huIL-2 led to a transient expansion of human CD45 + cells in the blood of NSG and NSG-(K b D b ) null (IA null ) mice engrafted with 10 3 10 6 PBMCs for 2 wk (Fig.…”
Section: Engrafted Human T Cells In Nsg-mentioning
confidence: 99%
“…3), we next determined whether administration of human recombinant IL-2 could modulate the T cell populations. We have previously shown that administration of a dsAAV8 vector encoding human IL-2 (dsAAV8-huIL-2) increased human regulatory T (T reg ) cells in NSG mice humanized by engraftment of human fetal liver and thymus [i.e., the BLT model (49)]. In the current study, injection of dsAAV8-huIL-2 led to a transient expansion of human CD45 + cells in the blood of NSG and NSG-(K b D b ) null (IA null ) mice engrafted with 10 3 10 6 PBMCs for 2 wk (Fig.…”
Section: Engrafted Human T Cells In Nsg-mentioning
confidence: 99%
“…34,35 Because human T cells are educated in autologous thymic tissues in the BLT model, it has been important in the investigation of human T cell development. 36,37 Furthermore, this model has had a great impact on the study of infectious diseases, especially HIV, as this model improves the colonization of lymphoid organs, together with the human reconstitution of the mucosal and gastrointestinal tracts. 35 In this model, BLT mice can recapitulate mucosal transmission of HIV via vaginal and rectal routes.…”
Section: Zeng Et Al 21mentioning
confidence: 99%
“…Furthermore, adeno‐associated virus delivery of human IL‐2 has been demonstrated to increase the engraftment of regulatory T cells in NSG‐BLT mice . Notably, however, in certain background strains there is already an unphysiologically high proportion of T regulatory cells, which can be undesirable when investigating responses to infections (Table ).…”
Section: Adaptive Immunity In Humanized Micementioning
confidence: 99%